Determinants of purchase intention to buy global brands cosmetic among millennial / Nur Ainul Mardiah Jamal - Jamal, Nur Ainul Mardiah (Faculty of Business and Management, 2019)
Since the past few decades, the cosmetic industry has been growing speedily and cosmetic industry is an industry that quick expanding globally. The increasing numbers of new cosmetic firms penetrating the market have thrived this beauty business and caused a greatly competitive environment. For that reason, cosmetic companies need to constantly develop their business activities with the aim to stay and draw the attention of new customers by creating values and meet their needs to comprehend and satisfy their customers. In Malaysia, the cosmetics industry is also rapidly growing at a yearly rate of 13% due to the number of working women are increasing, improved development and the rising of self-awareness as a result of education. The purpose of this research is to investigate the influence of quality, country of origin, brand image and emotional value on the purchase intention to buy global brands cosmetic among millennial. The researcher distributed the questionnaire to collect 150 responses from millennial-aged 16-36 years old in Melaka. Data collected were analyzed by using multiple linear regression. The results found that emotional value positively influenced the purchase intention to buy global brands cosmetic. However, quality, country of origin and brand image are not significant. The findings might advantage cosmetics firms and marketers to well comprehend essential factors affecting cosmetics purchase intention among Malaysian consumers in order to better strive in the global and the domestic market.